Two families with quadrupedalism, mental retardation, no speech, and infantile hypotonia (Uner Tan Syndrome Type-II); a novel theory for the evolutionary emergence of human bipedalism - Tan, Uner (Frontiers in Neuroscience, 2014)
Two consanguineous families with Uner Tan Syndrome (UTS) were analyzed in relation to self-organizing processes in complex systems, and the evolutionary emergence of human bipedalism. The cases had the key symptoms of previously reported cases of UTS, such as quadrupedalism, mental retardation, and dysarthric or no speech, but the new cases also exhibited infantile hypotonia and are designated UTS Type-II. There were 10 siblings in Branch I and 12 siblings in Branch II. Of these, there were seven cases exhibiting habitual quadrupedal locomotion (QL): four deceased and three living. The infantile hypotonia in the surviving cases gradually disappeared over a period of years, so that they could sit by about 10 years, crawl on hands and knees by about 12 years. They began walking on all fours around 14 years, habitually using QL. Neurological examinations showed normal tonus in their arms and legs, no Babinski sign, brisk tendon reflexes especially in the legs, and mild tremor. The patients could not walk in a straight line, but (except in one case) could stand up and maintain upright posture with truncal ataxia. Cerebello-vermial hypoplasia and mild gyral simplification were noted in their MRIs. The results of the genetic analysis were inconclusive: no genetic code could be identified as the triggering factor for the syndrome in these families. Instead, the extremely low socio-economic status of the patients was thought to play a role in the emergence of UTS, possibly by epigenetically changing the brain structure and function, with a consequent selection of ancestral neural networks for QL during locomotor development. It was suggested that UTS may be regarded as one of the unpredictable outcomes of self-organization within a complex system. It was also noted that the prominent feature of this syndrome, the diagonal-sequence habitual QL, generated an interference between ipsilateral hands and feet, as in non-human primates. It was suggested that this may have been